Characterization and Analysis of Flavonoid in Ethanol Extract and Purified Extract of Fringed Spider Flower (Cleome Rutidospermae Dc.) as Antioxidants - Christyaningrum, Prischilla; Utami, Nastiti; Desi, Alip (GLOBAL HEALTH SCIENCE GROUP, 2024)
The secondary metabolite profile of fringed spider flower or purple cleome (Cleome rutidospermae DC.) has not been widely explored. One of the secondary metabolites contained in purple cleome is flavonoids. Flavonoids have antioxidant, antibacterial, antidiabetic activities. Objective: This study aims to qualitative analysis of flavonoid, determine total flavonoid content, and antioxidant activity of ethanol extracts and purified extracts. Method: Purple cleome leaf was extracted with 96% ethanol using maceration method for 5 days, followed by extract purification stage. Qualitative identification of flavonoids using Wilstater and Taubeck methods. Identification of flavonoid compounds in the UV-Vis spectrum was based on the presence of typical cinnamoyl and benzoyl bands, determination of flavonoid content using aluminum chloride colorimetric method, and antioxidant activity test using DPPH method. Results: Qualitative identification of ethanol extract and purified extract of purple cleome have positive result contained flavonoids using the wilstater and taubeck tests. Identification of flavonoids with UV-Vis, the ethanol extract showed absorption of flavone, substituted flavonol 3-OH, and free flavonol 3-OH, while the purified extract showed absorption of flavone and free flavonol 3-OH. The ethanol extract and purified extract had total flavonoid content of 7.625±0.000 mg QE/g extract and 2.396±0.036 mg QE/g extract. Antioxidant activity results on ethanol extracts and purified extracts obtained IC50 values of 128.249±0.070 ppm and 86.513±0.042 ppm. Conclusions: The highest flavonoid content was found in the ethanol extract of purple cleome leaf. Flavonoid types in ethanol and purified extracts of purple cleome leaf indicated flavone and flavonol types based on the wavelengths of cinnamoyl and benzoyl. The strongest antioxidant category was found in the purified extract of purple cleome.